Affordances of Mobile learning in Higher Education - Yepez-Reyes, Veronica (2018)
Mobile learning or M-learning benefits from the ubiquity of ICTs, consequently it is not bounded in space and time. In this way, M-learning could foster connection and interaction “on the move”. M-learning addresses the way this type of education leads to the acquisition of meaningful learning. The aim of this article is to better understand the affordances of M-learning in undergraduate studies in Ecuador. By unfolding the varied affordances of M-learning, the outcomes suggest that blending formal instruction with informal learning leads to encouraging, accessible and cooperative effective and meaningful learning in any field of knowledge.